Iranian EFL learners’ realization of condolence: an interlanguage pragmatics study - Sharif, Maryam; Yarmohammadi, Lotfollah; Sadighi, Firooz; Yamini, Mortaza; Bagheri, Mohammad Sadegh (Colombian Applied Linguistics Journal, 2018)
This study was an attempt to examine Iranian EFL learners’ realization of the condolence speech act in English and to compare their realization with English native speakers’ (NSs) realization patterns. The study was further interested in investigating whether Iranian EFL learners’ realization of the condolence speech act is associated with their level of L2 proficiency. To this end, a Discourse Completion Test (DCT) was administered to 82 undergraduate Iranian EFL students in English. The participants were divided into three levels of language proficiency (elementary level, intermediate level, and advanced level) based on their scores on the Oxford Quick Placement Test (OQPT). For baseline comparisons, the EFL learners also received the translated version of the same DCT in Persian, and the English DCT was administered to 20 NSs of American English. The data were analyzed based on Elwood’s (2004) coding scheme. The results revealed that Iranian EFL learners had access to the same condolence strategies as English NSs, yet they differed in the semantic formulas, content, or forms they adopted to formulize their condolence expressions. In addition, level of L2 proficiency was found to be associated with Iranian EFL learners’ realization of the condolence speech act.